2017
DOI: 10.1063/1.4985885
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic Monte Carlo approach to study fluid transport in pore networks

Abstract: The mechanism of fluid migration in porous networks continues to attract great interest. Darcy's law (phenomenological continuum theory), which is often used to describe macroscopically fluid flow through a porous material, is thought to fail in nano-channels. Transport through heterogeneous and anisotropic systems, characterized by a broad distribution of pores, occurs via a contribution of different transport mechanisms, all of which need to be accounted for. The situation is likely more complicated when imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…Monte Carlo simulations [19,80] have been attempted, each with both promising features and drawbacks, to access longer length and time scales while accounting for fluid-rock interactions and the wide range of confined fluid states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monte Carlo simulations [19,80] have been attempted, each with both promising features and drawbacks, to access longer length and time scales while accounting for fluid-rock interactions and the wide range of confined fluid states.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bhandari et al [13] reported permeability as low as 2 nanodarcy, and anisotropy of 40 (ratio between permeability measured in two directions) for their samples, which consisted of 4% total organic content and contained large amounts of quartz, calcite, and clay. Measured shale permeability ranges from 0.1 to 1000 nanodarcy [12,14], and anisotropy from as little as 5 to 10000 or more [12,15], Starting from these experimental data, research has focussed on reconstructing three-dimensional volumes to map the pore space distribution and simulate permeability using, e.g., the Lattice Boltzmann Method [3,[16][17][18], stochastic modelling [19], or a combination of the Metropolis-Hastings and genetic algorithms [20].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…KMC has been successfully applied to catalysis, where a number of chemical reactions can occur simultaneously to transform reactants and intermediates into a variety of products, to describe transport in porous networks, as well as in many other applications. [187][188][189][190] Experimental validation. It is necessary to validate the quantitative understanding achieved via fundamental research.…”
Section: Some Open Fundamental Multidisciplinary Questionsmentioning
confidence: 99%
“…The coordination number z is kept constant and equal to 4, 3 3 as we consider rectangular twodimensional (2D) networks. Building on previous work on KMC, 29 the term "voxel" refers here to a single cell of a matrix representing a pore network. For Eq.…”
Section: Emtmentioning
confidence: 99%
“…28 Alternatively, KMC can follow molecular trajectories and yield permeability calculations with satisfactory accuracy and orders of magnitude lower computational cost compared to Molecular Dynamics (MD) simulations. 29,30,31 The promise of fast and straightforward estimates makes deterministic approaches appealing to practitioners. However, considering the nature of shale formations (high heterogeneity and a significantly large percent of micro-porosity due to the contribution of small pores 32 ) the deterministic approaches considered here may be inapplicable.…”
Section: Introductionmentioning
confidence: 99%